Divinations - Kuo, Michelle (Intermédialités / Intermediality, 2009)
The essay “Divinations” focuses on Robert Rauschenberg’s Oracle (1962-1965), a work whose making and display entailed close collaboration between the artist and the engineers Billy Klüver and Harold Hodges, both of Bell Laboratories. The piece stemmed from Rauschenberg’s interest in sound, sculptural form, and radio networks: it housed ten radios and speakers in various sculptural elements constructed from found metal objects, including ducts, window frames, a bathtub, and a car door. Audience members could turn dials that indirectly modified the volume and tuning of the radios. Walking through the sculptural installation, one experienced shifting acoustic, spatial, and visual effects. This text seeks to understand how the interactions between artist and engineers—and between sound sculpture and viewers—engaged systems of industrial and postindustrial production, broadcast radio, and audiovisual reception.